ARAB STUDENT-TEACHERS’ PROFESSIONAL IDENTITIES BETWEEN THE PERSONAL AND CULTURAL - Hayik, Rawia (PEOPLE: International Journal of Social Sciences, 2018)
Everyone not only has a story but also has a right to tell their story” (Bamberg, 2012, p. 79). Grounded in theoretical discourses that underscore the significant role of narrative in teachers’ identity construction and disclosing (Connelly and Clandinin, 1999), this study invites a group of 15 third-year female students from the English department at an Arab teacher-education college in Northern Israel to narrate their stories of meaningful experiences and life events that have contributed to shaping their professional identities. Students-teachers’ narratives are collected in a two-phase process to illuminate the various experiences that have contributed to shaping their identities. Narrative and discourse analyses of students’ narratives shed light into the individual, professional, and socio-cultural factors that have shaped their professional identities as English teachers. The significance of the study lies in contributing to the scarce literature on identity construction of a population often absent from professional-identity research (female and minority Arab EFL student-teachers). Additional contributions are raising students’ awareness of the resources and constraints in their history that have affected their professional development as well as raising my awareness as teacher educator to my students’ experiences and helping me to become more tuned to their voices and struggles.